The Use and Impact of Virtual Platforms in the Learning Process: Experience with Students of Criminology and Police Science at Universidad Estatal a Distancia Costa Rica - Vargas-Cubero, Ana Lorena (2018)
The objective of this study is to determine how the use of Moodle online educational platform helps students of Criminology and Police Sciences to learn. A high percentage of the students from these majors work and study facing adverse conditions. Improvements in mediation, variety of resources, and autonomous learning may turn into meaningful learning opportunities for students. The methodology of this study is based on a quantitative approach by means of a sample survey. A nineteen-item semi-structured questionnaire was administered to fifty students to explore aspects related to working order, academic performance, and online course mediation. Forty-one out of fifty participants responded evaluating two courses from the Cátedra de Ambiente, Política y Sociedad [Chair of Environment, Politics, and Society] and three courses from the Cátedra de Trabajo Social [Chair of Social Work] that were offered during the first quarter of 2016. The gathered information was tabulated to facilitate its analysis. The results indicate that the use of online platforms and technology can be used to improve meaningful learning. However, the resources do not have an incidence without well-structured courses, resources, and the appropriate mediation from instructors.